Comparison of Low-Noise Air Nozzles: A Pilot Study. (September 2017) - Salar, Menekse; Capanoglu, M. Fehmi; Bandekar, Anjaneya; Sesek, Richard F.
Excessive noise is a global occupational health hazard with considerable social and physiological impact, including noise-induced hearing loss (NIHL) (Nelson et al., 2005). Noise is one of the most common occupational hazards in American workplaces. This study was performed in the Occupational Safety and Ergonomics Program's Biomechanics Laboratory at Auburn University. The main purpose of this study was to compare the noise levels made by different air nozzles actually used by a bakery facility to nozzles whose manufacturers purported that they produce significantly less noise. Noise levels were determined using a sound level meter, which was positioned at ear level at distances of 5 and 10 feet. At the factory, air pressure ( 100 psi) was used to push product downstream and to speed product cooling. The nozzles used were simple pipes or traditional air nozzles with side venting, but not of a "low noise" design. Two nozzles used by the factory were compared to three quieter nozzles. Nozzles were tested for both noise level and for air pressure (pushing force).